Theoretical Investigation of the Te4Br2 Molecule in Ionic Liquids. Issue 1 (19th December 2016) - Elfgen, Roman; Hollóczki, Oldamur; Ray, Promit; Groh, Matthias F.; Ruck, Michael; Kirchner, Barbara
Abstract : Material synthesis in ionic liquids, at or near room temperature, is currently a subject of immense academic interest. In order to illuminate molecular‐level details and the underlying chemistry, we carried out molecular simulations of a single Te4 Br2 molecule dissolved in the ionic liquid 1‐ethyl‐3‐methylimidazolium chloride, as well as in the ionic liquid mixed with aluminum chloride. Although the ethyl side chain is much too short to show detailed microheterogeneity, significant structuring with the small chloride anions is seen in case of the pure ionic liquid. In the case of the mixture, formation of larger anionic clusters is distinctly observed and analyzed. Due to the tendency of ionic liquids to dissociate, there is a pronounced shift to elongated Te–Br distances in both investigated solvents. However, only in the AlCl3 ‐containing liquid, we observe the reaction of the open chain‐like Te4 Br2 molecule to a closed square‐like Te4 Br + and AlCl3 Br – ion. The molecular arrangement of the [Te4 ] 2+ unit shows negligible deviation from that in the experimental crystal structure. Abstract :